Analisis Wacana Representasi Efektivitas Pembelajaran Daring dan Luring di Era Covid-19 Pada Situs Berita Kumparan.com - Abadi, Totok Wahyu (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2024)
Much has changed since the COVID-19 pandemic, especially in the field of education. Many educational institutions have turned to alternative learning methods since the pandemic was triggered by quarantine and social constraints. Using online or online media is one of the methods of controlling the COVID-19 pandemic. It's about distance education, which is used to keep social distances and stop the spread of the virus. Every method of education, whether online or offline, has its advantages and disadvantages. The aim of this study is to find out how students create discourse about how effective online learning and luring on Kumparan.com during the COVID-19 pandemic. Data is analyzed using qualitative methods. In this study, Theo Van Leeuwen used discourse analysis, which looked at the text from the point of view of how attachments consisted of text or news. This investigation found that Kumparan.com's content used exclusion and inclusion strategies.